Hasil Uji Fitokimia: Kandungan Royal Jelly Apis Mellifera Sebagai Persiapan Suplemen Prakonsepsi - Nurrahmi Umami; Indah Raya; Andi Nilawati Usman; Ninik Azizah; Yudiarsi Eppang (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: This study aims to identify chemical bonds and chemical compounds using the FTIR method, as well as using phytochemical tests to assess what ingredients are contained in royal jelly.Methods: This study was a laboratory study conducted at the MIPA Chemistry Laboratory and the Biochemistry Laboratory, Faculty of Mipa, Hasanuddin University, Makassar. The sample used in this study was royal jelly obtained from the Forestry Laboratory of Hasanuddin University Makassar. Examinations used in the form of FTIR test (Foourier Transform Infrared) and Phytochemical Test (flavonoids and phenolic).Results: royal jelly apis mellifera contains flavonoids and polyphenols which play an important role as preconception supplements as evidenced by the results of phytochemical and FTIR tests.Conclusion: This study contains flavonoids and polyphenols in royal jelly which are antioxidants, both of which are used as ingredients that can be used in the production of initial products and as supplementary supplement care for preconception, preventing several diseases resulting from lack of antioxidants in the body.